Sustainable Care: Care as a Communal Virtue in Early Childhood Education - Gunnar Magnus Eidsvåg (ECNU Review of Education, 2022)
Purpose Care is a core concern for early childhood education and care (ECEC) institutions. Care may be understood as a basic form of interaction and a foundational need for human beings. For these reasons, care also presents challenges for ECEC staff. The staff must seek practical solutions to problems that philosophers have raised on a theoretical basis concerning ethical traditions, such as the ethics of care. These are the problems of justice, parochialism, and self-sacrifice. Design/Approach/Methods This article develops a theory concerning the ethics of care in ECEC institutions. The theory is informed by qualitative interviews with ECEC teachers reflecting on their caring practices. The study is therefore located at the intersection of normative ethics and applied ethics. In seven in-depth interviews, the informants discussed how to create a caring ECEC environment that is fair and possible to maintain over time. Findings Through analyzing the interviews, I found that caring practices that work toward these ideals can be described as sustainable care. These practices take care of all the children and provide the staff with opportunities to regain the strength they need to create a caring and educating setting. Originality/Value The theory this article develops makes ethics of care applicable and practically relevant to ECEC institutions.